MENDEKLAMASIKAN PUISI PRIBADI MELALUI AKTIVITAS PEMBELAJARAN PERSONALIZED LEARNING - Edhy Rustan; Windi Yanti; Lilis Suryani (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
Reciting Personal Poetry Through Personalized Learning Learning Activities.The purpose of this study is to describe the application and formulation of personalized learning in reciting personal poetry. The type of research used is development with a multiphase design that combines the mixed method approach by Creswell. The research subjects were grade IV students and SDN 20 Battang, Palopo City teachers. Methods of data collection through questionnaires, observation, interviews, and documentation. The research results show that learning steps, instructional verbs, and scoring rubrics do not support the achievement of indicators. The formulation of personalized learning model learning activities that can be carried out in reciting personal poetry is an initial assessment of student characteristics, identification of individual needs, making personal poetry, training, and individual guidance, providing space and support, creative expression, staging and reflection, and continuous evaluation.